A Comparative Study on the Effect of Black Cohosh and Salvia on Hot flashes in Postmenopausal Women - Seyedeh Zahra Masoumi; Arezoo Shayan; Roya AhmadiNiya tabesh; Hassan Ahmadinia; Shirin Moradkhani; Maryam Farhadian; Reyhaneh Ebrahimi; Farzaneh Soltani (Mashhad University of Medical Sciences, 2019)
Introduction: Vasomotor disorders including hot flushes are of the most painful symptoms of menopause and affect the women's quality of life. This study was performed with aim to compare the effects of Salvia and Black Cohosh on hot flashes in postmenopausal women. Methods: This randomized clinical trial was performed on 80 postmenopausal women referring to Hamadan health centers in 2016. After reviewing the inclusion criteria, the subjects were randomly assigned to two groups of black cohosh (n=40) and salvia (n=40) and consumed the medicine for 2 months. The researcher-made checklist including duration, severity and frequency of hot flashes was completed before the intervention and within 8 weeks by the subjects. Data were analyzed by SPSS software (version 20) and t-test, Mann-Whitney U, Friedman and Wilcoxon tests. P<0.05 was considered statistically significant.  Results: Salvia plant had a significant effect on the reduction of hot flashes from the second week (p<0.001), but the effect of Black Cohosh was not significant except for the third week. The intensity of hot flashes decreased in the salvia group after the first week and a significant difference was observed with before taking the drug (p<0.000). In black cohosh group, the intensity of hot flashes decreased after the fourth week, and there was a significant difference with before taking the drug (P<0. 000). Silvia plant was effective on the number of hot flashes over time, and the number of hot flashes changed in different weeks (over time), but for black cohosh group, the number of hot flashes was not significantly changed over time . Conclusion: Salvia compared with black cohosh more reduces the duration, severity and frequency of hot flashes in postmenopausal women. Therefore, since it is non-invasive and is a herb, it is recommended to use this plant to reduce the symptoms of hot flashes.